MENINGKATKAN HASIL PEMBELAJARAN SBDP MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE STAD PADA SISWA KELAS I DI SD NEGERI 001 DESA BARU KECAMATAN SIAK HULU KABUPATEN KAMPAR - Marladiana Marladiana (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
This research is a classroom action research conducted in SD Negeri 011 Desa Baru. The study applied the Cooperative type STAD learning model. The subjects of this study were students in the class I SD Negeri 011 Desa Baru. The results showed that the SBDP learning outcomes had increased. This is seen from the increase in the aspect of knowledge (cognitive) of 15.7% with the final value of class 85.2 and included in the excellent category. Then in the aspect of skills (psychomotor) an increase of 7.38% with a final grade average of 81.4 and included in the good category. Furthermore, in the aspect of attitude (effective), there was an increase of 11.04% with the average grade of the final class 80.4 and included in the good category.